MEKANISME KLORINASI EUGENOL MENGGUNAKAN KLORIN (CL2) DENGAN KATALIS FECL3 DALAM PELARUT DIKLOROMETANA - Sayekti, Endah; Silalahi, Imelda H; Awalliah, Emy (Jurnal Sains dan Teknologi Kimia, 2013)
Chlorination of eugenol by chlorine with catalyst of FeCl3 in dichloromethane solvent had been performed. Chlorination was carried out at 2oC for 5 hours. The reaction produced dark brown clot which was soluble in methanol, acetone, ethyl acetate, dichloromethane and chloroform but insoluble in aquadest. An infrared analysis gave the chlorobenzene groups at 1095.57-1072.42 cm-1. The NMR1H showed the CHCl and CH2Cl groups at 3.2884-3.0185 ppm and NMR13C showed carbon as C-Cl at 100-20 ppm. GC-MS spectrum analysis showed there are four dominant products with the time retention at 28.650; 29.300; 32.383 and 37.242. Result of the spectroscopy analysis showed that the main coumpound of eugenol chlorination were 4-(2,3-dichloroprophyl)-2-methoxyphenol (24,67%); 4-(2-chloroprophyl)-6-chloro-2-methoxyphenol(20,57%); 4-(2,3-dichloroprophyl)-6-chloro-2-methoxyphenol (13,65%) and 3,6-dichloro-4-(2,3-dichloropropyl)-2-methoxyphenol or 5,6-dichloro-4-(2,3-dichloropropyl)-2-methoxyphenol  (9,92 %). Therefore, based on all analysis which were done, it can conclude that   chlorination of eugenol using chlorine catalyzed by FeCl3 in dichloromethane cause addition and aromatic electrofilic substitution. Key Word: Eugenol, Chlorination, FeCl3, Dichloromethane